Simultaneous detection of equine sperm subpopulations with different phenomes using a novel staining technique - NILENDU PAUL; THIRUMALA RAO TALLURI; KAMARAJ ELANGO; KATHAN RAVAL; PRADEEP NAG; YASH PAL; LEGHA RAM AVTAR; T K BHATTACHARYA; ARUMUGAM KUMARESAN (Indian Journal of Animal Sciences)
Nowadays, there is an increased demand for liquid and frozen semen of stallion as the breeding registries have allowed artificial inseminations. Therefore, it is important to ensure the quality of stallion semen because it will be used for inseminating a large number of mares. Traditionally, various dyes were being used for assessing individual sperm functional parameters which is laborious, time consuming and require large quantity of samples. Recently, fluorescent dye-based sperm quality assessment techniques are replacing the conventional staining procedures and are proving to be more accurate, reliable and time efficient. In the current study, we developed fluorescent dye based triple staining methods for simultaneous detection of sperm vital parameters i.e viability, acrosome integrity, mitochondrial membrane potential and mitochondrial reactive oxygen species. Cryopreserved semen from 6 stallions were used for the current study. Through the standardized triple staining methods, we identified various sperm subpopulations (seven sub populations in FITC-PNA+MitoSox+Hoechst 33258 and four subpopulations in FITC- PNA+JC-1+Hoechst 33258), all of which cannot be assessed using single or dual staining techniques. We therefore conclude, that triple staining can be useful for simultaneous assessment of important sperm functional parameters of stallion spermatozoa in a cost and time effective manner.